Enhancing the Value of Bajing Coffee: A Branding Training and Assistance at Girimoyo Village - Novin Farid Styo Wibowo; Moch Fuad Nasvian; Aditya Dwi Putra Bhakti; Radityo Widiatmojo (LPPM Universitas Ma Chung, 2023)
One of the sectors that contribute to the Indonesian economy is agriculture, forestry, and fishery with around 13.28% of the Gross Domestic Product (GDP). Among them, coffee is known to be one of the essential commodities. Girimoyo village, one of the known coffee producers in Malang Regency, has a special coffee product called Bajing Coffee. Pamanjur Coffee Processor, one of the coffee production businesses, wants to make Bajing Coffee more popular. However, Pamanjur Coffee Processor fails to recognize the consumer and that makes the business grow slowly. Hence, Pamanjur Coffee Processor needs to raise people’s awareness of their products by methods that suit youngsters, especially through appealing social media content. As a result, this community service aims at helping Pamanjur Coffee Processor to gain more awareness. This community service program uses several methods, assessment, training, and assistance. The result shows that Pamanjur Coffee Processor did not have the “energy” to spend on the branding process of Bajing Coffee, but all the skills provided by the community service team are used to develop the identity and promotion of their cafe business line. As a result, this community service program was successful at the skill transfer level but failed to increase the branding of Bajing Coffee.